Perancangan Sistem Keamanan Pintu Toko Berbasis Internet Of Things (Studi Kasus : Toko Chantika Shoes) - Alman Arapa; Sigrid Tamriesfatno; Sarliadin Sarliadin; Sarwono Sarwono; Ahmad Musawir (Pusat Riset dan Inovasi Nasional, 2026)
Door security is a vital aspect in ensuring safety and protecting assets, particularly in commercial buildings such as retail stores that are vulnerable to unauthorized access outside operating hours. Along with the rapid advancement of digital technology, security systems are required to go beyond conventional mechanisms by providing remote monitoring and control capabilities. This study aims to design an Internet of Things (IoT)–based door security system as a solution to enhance security at Chantika Shoes Store. The research adopts a system design method that includes requirements analysis, hardware design, software design, and system workflow development. The proposed system utilizes IoT devices and sensors to detect door activity and transmit real-time information to users via an internet network. Through the integration of hardware and software components, the system enables continuous monitoring of door conditions, instant notification delivery in the event of unauthorized access, and remote control of the door locking mechanism using a mobile application. This approach allows store owners to respond quickly to potential security threats and improves efficiency compared to conventional security systems. The designed system is expected to serve as a reference for developing more effective and efficient IoT-based door security solutions that meet the security requirements of retail businesses in the modern technological era